2019
DOI: 10.1590/s1980-6574201900020017
|View full text |Cite
|
Sign up to set email alerts
|

Tactical efficacy and offensive game processes adopted by Italian and Brazilian youth soccer players

Abstract: To analyze success and failure of offensive sequences and the adopted offensive method in under-15 (U-15) and under-17 (U-17) soccer players. Methods: The sample was composed of 218 offensive sequences performed by U-15 and U-17 players selected from 28 matches, being 18 matches of an Italian team and 10 matches of a Brazilian team. All offensive sequences which ended in finalization were selected for the analysis. Using observational methodology, an adapted ad hoc observational instrument was built with the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Machado, Barreira & Garganta (2013) reported that in national teams of the 2010 World Cup the offensive efficacy was not a reflection of a certain duration of the strings (short or long) or of playing styles (direct or indirect). Borges et al (2019) reinforce this idea by concluding with teams of youth Brazilian and Italian football players that it is possible to be effective by opting for different styles of offensive construction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Machado, Barreira & Garganta (2013) reported that in national teams of the 2010 World Cup the offensive efficacy was not a reflection of a certain duration of the strings (short or long) or of playing styles (direct or indirect). Borges et al (2019) reinforce this idea by concluding with teams of youth Brazilian and Italian football players that it is possible to be effective by opting for different styles of offensive construction.…”
Section: Discussionmentioning
confidence: 91%
“…A considerable part of the studies on tactical actions have adopted the evaluation of the players' performance based on unilateral criteria, which may neglect the interaction of different parameters that cooperate for the manifestation of tactical qualities (Folgado, Bravo, Pereira & Sampaio, 2018). In order to fill part of this gap, recent studies with multilateral perspectives aimed to understand the effects of contextual aspects, such as match location (Caballero, García-Rubio & Ibáñez, 2017;Pic & Castellano, 2017), quality of the opponent (Caballero, García-Rubio & Ibáñez, 2017;Gómez, Mitrotasios, Armatas & Lago-Peñas, 2018;Errekagorri, Castellano & Echeazarra, 2020), competitive level (Borges et al, 2019), and match status Praça, Lima, Bredt, Sousa, Clemente & Andrade, 2019) on tactical actions by players and teams.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded matches refer to the teams. Following the data collection, the videos were evaluated using Match Vision Studio Premium® software, which has been used as a reference in conducting studies with observational methodology 9,10,[28][29][30] .…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, there has been an increase in the number of studies that aim to investigate sports performance during a soccer match. Among the variables that can be studied, the distance covered, type of activity [1][2][3] , intensity 4 , comparisons between different game positions 5,6 , and efficiency of actions and technical performance during a match [7][8][9][10] have gained prominence in the scientific literature, providing important information to professionals involved in this context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation